PENGARUH INDEPENDENSI, INTEGRITAS, OBYEKTIFITAS, DAN KOMPETENSI INSPEKTORAT TERHADAP KUALITAS HASIL AUDIT KEUANGAN DAERAH (Studi Empiris pada Inspektorat di Provinsi Kepulauan Riau) - Adlina Fathnun; Kirmizi Kirmizi; Mudrika Alamsyah Hasan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research aimed to determine the influence independency, integrity, objectivity, and competency, a positive influence on audit quality. In This research, researcher examined the quality of audit in some Inspectorates in Kepulauan Riau Province by using independent variables that are independency, integrity, objectivity, and competency. The population in this research are all auditors who worked on the Inspectorates in Kepulauan Riau Province. Sampling was conducted using a purposive sampling method and number of samples of 52 respondents. Primary data collection method used is questionnaire method. Data analysis technique used in this research is multiple regression analysis. The results of this research showed that integrity, objectivity, and competence have a positive and significant influence on audit quality. Simultaneously, all independent variables have a positive and significant influence on audit quality. Researcher suggested for future research in order to add more variable and then to extend the population.Keywords: independency, integrity, objectivity, competency, quality of audit result.